Manajemen Strategi Islam Dalam Meningkatkan Partisipasi Anggota Dan Bikers Pada Event Jambore Daerah Hmpc Sumatra - Muhammad Rizki; Mohd. Aji Isnaini; Hartika Utami (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of Islamic strategic management in increasing the participation of members and bikers at the Regional Jamboree event of the Honda Megapro Club (HMPC) Sumatra. This research is motivated by the importance of applying Islamic values in community organization management to enhance member involvement and participation in organizational activities. Islamic strategic management in this study includes the functions of planning, organizing, actuating, and controlling based on the values of deliberation (musyawarah), trustworthiness (amanah), justice, and Islamic brotherhood (ukhuwah). This study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with HMPC Sumatra administrators and members, observation during the Regional Jamboree event, and supporting documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of Islamic strategic management plays a significant role in increasing the participation of members and bikers at the HMPC Sumatra Regional Jamboree. The value of deliberation is applied in decision-making processes, trustworthiness is reflected in task distribution among committee members, and ukhuwah strengthens solidarity among members and chapters. Supporting factors include management commitment, effective communication, and organizational solidarity. However, challenges remain, such as time limitations and varying levels of participation among chapters. Overall, Islamic strategic management has proven effective in enhancing member and biker participation in organizational activities